Menyikapi Tren Fast Fashion Perspektif Al-Qur’an (Analisis Maqāṣid Al-Qur’ān Ibn ‘Āsyūr) - Nurhayati, Nurhayati; Afifullah, Afifullah (IAIN Madura, 2023)
The trend of fast fashion is one of the popular trends the public, especially among teenagers. They tend to follow these trends without seeing the benefits obtained. They usually buy an item spontaneously without planning so that it tends to give birth to a consumptive attitude. They will do all kinds of things to get the items they want. In addition, following fast fashion trends also has a negative impact on the environment. This article is literature research, using Ibn 'Āshūr's maqāṣid al-Qur'ān approach. It will elaborate on the interpretation of surah al-Anbiyā' (21) verse 37, al-Nahl (16) verse 78 and al-Hadīd (57) verses 20-21 and how to address the fast fashion trend from the Qur'anic perspective with Ibn 'Āshūr's maqāṣid al-Qur'ān analysis. The Qur'an provides a solution as one of the attitudes that can be done in dealing with the fast fashion trend that is rampant, namely: First, not being hasty (QS. al-Anbiyā' (21): 37). Second, examining on how much benefit will be obtained and how much harm will be caused (QS. al-Nahl (16): 78) in following the fast fashion trend. Third, adjusting the life style to the ability of self (QS. al-Hadīd (57): 20-21).